1969
DOI: 10.1136/jmg.6.4.379
|View full text |Cite
|
Sign up to set email alerts
|

Congenital extrahepatic biliary atresia in two brothers.

Abstract: Congenital atresia of the extrahepatic biliary system has seldom been described in more than one member of a family. This note records the condition in two brothers. Case ReportsThe unequivocal diagnosis was made in both brothers at operation and therefore details of the special investigations are not given. The results of these were, however, similar to those frequently described for sporadic cases of the same condition. between the fifth and sixth months of the pregnancy which had been otherwise normal. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

1975
1975
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…The larger studies of this condition (Hsia etal., 1958;Danks and Bodian, 1963;present study) contain no family with a second case among a total of 142 families. Several papers have reported individual families claimed to contain 2 or more babies with EHBA (Nevin et al, 1969). However, careful study of the patients reported shows that some date from the period before NNH was distinguished from EHBA and that most of the more recent cases have suffered from the unusual entity of EHBA plus IHB3A.…”
Section: Discussionmentioning
confidence: 99%
“…The larger studies of this condition (Hsia etal., 1958;Danks and Bodian, 1963;present study) contain no family with a second case among a total of 142 families. Several papers have reported individual families claimed to contain 2 or more babies with EHBA (Nevin et al, 1969). However, careful study of the patients reported shows that some date from the period before NNH was distinguished from EHBA and that most of the more recent cases have suffered from the unusual entity of EHBA plus IHB3A.…”
Section: Discussionmentioning
confidence: 99%
“…Since that time, at least 11 pedigrees of familial EHBA have been reported in which the diagnosis was confirmed by laparotomy and/or autopsy in one or more affected individuals [Glaister, 1879;Hopkins, 1941;Krauss, 1964;Nevin et al, 1969;Parker, 1901;Rumler, 1961;Sweet, 1932;Whitten and Aide, 19521. Pathologic findings of fibrotic ductal remnants from the biliary tree, atretic or absent ducts, bile stasis, inflammation, and often the fibrotic changes of cirrhosis reported in familial cases are indistinguishable from those of sporadic cases [Hopkins, 1941 ;Krauss, 1964;Nevin et al, 1969;Sweet, 1932;Rumler, 1961;Whitten and Aide, 19521. Danks and Bodian [1963] found no other cases among first-and second-degree relatives of 47 infants with EHBA.…”
Section: Discussionmentioning
confidence: 98%
“…The overall incidence in the United States is estimated at 0.65/10,000 live births [Morecki et al, 19821. While most cases are sporadic, familial occurrence has been reported [Glaister, 1879;Hopkins, 1941; Krauss, 1964;Nevin et al, 1969;Parker, 1901; R u d e r , 1961;Sweet, 1932; Thomson, 1891 Thomson, , 1892 Whitten and Aide, 19521. We report 2 additional sibships in which EHBA has recurred.…”
mentioning
confidence: 97%
“…We have made a survey of the English literature concerning the familial occurrence of BA to accumulate 44 cases from 20 families [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The pattern of occurrence was exclusively in the patient's brother or sister.…”
Section: Discussionmentioning
confidence: 99%